Comparison of observed equatorial spread-F statistics between two longitudinally separated magnetic equatorial stations and the IRI-2016 model during low and high solar activities. Issue 6 (15th March 2022) - Thammavongsy, P.; Supnithi, P.; Myint, L.M.M.; Sripathi, S.; Hozumi, K.; Lakanchanh, D.
Abstract: This study compares the equatorial spread-F (ESF) statistics in equinoctial months at two stations near the magnetic equator and longitudinally separated: Chumphon (CPN) station (10.7°N, 99.4°E; geomagnetic latitude: 3.0°N), Thailand and Tirunelveli (TIR) station (8.73°N, 77.7°E; geomagnetic latitude: 0.32°N), India. The ionogram images are manually scaled at every 10 min and 15 min during the low solar activity (LSA) in 2008 and the high solar activity (HSA) in 2014. In particular, the range-type spread F (RSF) statistics are extensively analysed. We study the ESF occurrence percentages, ESF durations, and ESF day-to-day variabilities. At both stations, the percentages of the ESF occurrences are generally higher as the F10.7 solar flux values increase, therefore, resulting in more occurrences in HSA than LSA. The percentages of the ESF occurrences could reach up to 50% and 90% during LSA and HSA, respectively. The post-midnight ESF occurrences are more frequent at TIR station than CPN station. The onset time analyses of ESF events show that during HSA (2014), the ESF onsets at TIR station are earlier than CPN station by 15 min to 1 h and as frequent as 72% in each month. During LSA, the long ESF durations are observed at TIR station more frequently than at CPN station. In addition, the comparison between the observations and the predictions of the IRI-2016 model shows that the overestimations of the IRI-2016 model are up to 33% during LSA, but underestimations of the model are up to 25% during HSA.